Enhanced efficiency and stability of scalable spray-coated perovskite solar cells with ionic liquid additives. Issue 21 (6th October 2022) - Yang, Shun-Hsiang; Tsai, Chia-Hao; Wang, Xiao-Feng; Lee, Tai-Chou; Liu, Cheng-Liang
Abstract : Ultrasonic spray deposition of large area and pinhole-free perovskite films can be realized with the help of ionic liquid 1-butyl-3-methylimidazolium (BMIMBF4 ) as the additive. Abstract : The scaling up of perovskite films to generate prototypes with large surface area requires the development of scalable solution-processing techniques along with the optimization of precursor solution formulations to achieve enhanced performance and stability. Herein, high-quality and uniform perovskite films are realized by ambient ultrasonic spray deposition without the need for an antisolvent by using various amounts of the ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate (BMIMBF4 ) as the additive. The concentration of BMIMBF4 in the precursor solution is found to affect the morphologies and photoexcited lifetimes of the resulting spray-coated films. With the addition of the optimal amount of BMIMBF4 (0.30 mol%) and the use of vacuum-assisted solvent extraction, the power conversion efficiency of the device reaches 17.43% with negligible hysteresis, and over 86% of the initial efficiency is retained after 386 h of operation under ambient conditions. This demonstrates that the use of a limited amount of ionic liquid additive can help to improve the crystallinity and reduce the trapping state density of the perovskite film, and to suppress the formation of PbI2 during the perovskite crystallization process. However, higher BMIMBF4 contents lead to negative effects on the perovskite morphology. Finally, the perovskite film formed from the 0.30 mol% BMIMBF4 -containing solution is scaled to a large area of 5 × 10 cm 2 and cut into 8 samples to achieve a consistent device performance with a power conversion efficiency (PCE) of 14.83 ± 0.62%. These findings demonstrate that the rational control of the additive-containing perovskite ink composition and upscaling of the thin film deposition is essential for the large-scale manufacturing of perovskite layers for future commercialization of perovskite photovoltaics.